A Consensus on Acne Management Focused on Specific Patient Features. Issue 4 (July 2014) - Lynde, Charles; Tan, Jerry; Andriessen, Anneke; Barankin, Benjamin; Dutil, Maha; Gilbert, Martin; Hong, Chih-ho; Humphrey, Shannon; Rochette, Linda; Toole, Jack; Thomas, Richard; Vender, Ronald; et al.
Background: Most treatment guidelines for acne are based on clinical severity. Our objective was to expand that approach to one that also comprised individualized patient features: a case-based approach. Methods: An expert panel of Canadian dermatologists was established to develop demographic and clinical features considered to be particularly important in acne treatment selection. A nominal group consensus process was used for inclusion of features and corresponding appropriate treatments. Results: Consensus was achieved on the following statements: follicular epithelial dysfunction contributes to acne pathogenesis; inflammation from underlying disease(s) or prior treatment may impact further patient management; management focusing on specific patient features and on addressing psychosocial factors, including impact on quality of life, may improve treatment adherence and outcomes; and case-based scenarios are a practical approach to illustrate the effect of these factors. To address the latter, eight case profiles were developed. Conclusions: Management of acne should be based on multifactorial considerations beyond clinically determined acne severity and should include patient-reported impact, gender, skin sensitivity (including preexisting dermatoses), and phototype.